2001
DOI: 10.1007/s004250000422
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of non-specific permeability and H + -ATPase inhibition induced in the plasma membrane of Nitella flexilis by excessive Cu 2+

Abstract: Effects of Cu2+ on a non-specific conductance and H+-ATPase activity in the plasma membrane of the freshwater alga Nitella flexilis L. Agardh was studied using a conventional microelectrode voltage-clamp technique. We show that a Cu2+-induced increase in the non-specific conductance is related to the formation of pores in the plasma membrane. Pore formation is the result of unidentified chemical reactions, since the Q10 for the rate of increase of conductance over time was about 3. Various oxidants and antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…The plant plasma membrane (PM) can be regarded as the first structure that is a target for heavy-metal toxicity. An increase in permeability related to membrane damage is observed in plants that have been subjected to heavy-metal stress (De Vos et al , 1991, 1992; Demidchik et al , 1997, 2001; Murphy and Taiz, 1997; Murphy et al , 1999). One of the physiological responses to excess Cu is K + efflux from the roots.…”
Section: Introductionmentioning
confidence: 99%
“…The plant plasma membrane (PM) can be regarded as the first structure that is a target for heavy-metal toxicity. An increase in permeability related to membrane damage is observed in plants that have been subjected to heavy-metal stress (De Vos et al , 1991, 1992; Demidchik et al , 1997, 2001; Murphy and Taiz, 1997; Murphy et al , 1999). One of the physiological responses to excess Cu is K + efflux from the roots.…”
Section: Introductionmentioning
confidence: 99%
“…Small changes in pump activity are thought to be important for many aspects of plant growth and development. For example, many studies have found changes in pump activity in response to a variety of environmental conditions, including salt stress, hormones, light, and pathogens [5,6]. The regulation of H + -ATPase activity not only allows nutrient uptake in plant cells but also controls water fluxes in stomatal guard cells and to pulvinar motor cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…[615] It has been reported that an increase in the activity of Na, K + ATPase is partly responsible for the two major opiate effects in the brain, which create hyper polarization in the membrane and also inhibition of neurotransmitter release. [14] The AA dose dependently decreases the analgesic effect of morphine in mice,[19] and it may reduce the analgesic effect of morphine in patients. These results, along with others’ knowledge, show that AA modulates the synaptic action of dopamine and glutamate, which suggests that even very high doses of AA, which are known to be non-toxic, may be used with dopaminergic antagonist drugs, to treat the morphine-abstinence syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[1112] Both the glutamatergic and dopaminergic systems are involved in the dependence and tolerance of morphine and morphine withdrawal syndrome signs,[13] and all these treatments are majorly affected by AA. [1415] From the previous studies it is not clear as to what dose of AA can prevent tolerance to opioids (especially morphine). Therefore, in this investigation we endeavor to determine the effect of low and high doses of AA on self-administration of morphine as well as on morphine withdrawal symptoms, in rats.…”
Section: Introductionmentioning
confidence: 99%